CLONING AND EXPRESSION OF LACCASE GENE PRODUCED FROM Bacillus subtilis ZHR IN E. coli - & et al., Hassan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
Ten  isolates of  Laccase producing bacteria were obtained from 50  isolates belongs to Bacillus sp. These isolates were isolate  from different local areas of soil  in baghdad.The  isolates were subjected to primary screening , and  revealed  high production of enzyme based  on consumed  time  during the reaction with syringaldazine (  SGZ )  reagent at 37 ° C. These isolates were  subjected to secondary screening. The results revealed that isolate 136  was the best producers with highest enzyme activity of 47.0 U/ml.   Identification of this isolate was achieved by studying morphological, microscopic characteristic , Vitek2 compact system and  studying  gene sequencing  analysis of 16S rRNA gene .The results  revealed that the isolate was belongs to Bacillus subtilis and identified as  Bacillus subtilis ZHR. The laccase gene from Bacillus subtilis ZHR was extracted and amplified by PCR technique, then cloned  in expressed  Escherichia coli to produce  biologically active enzyme with enzyme activity of 108.6  U/ml and specific activity 332.14 U/mg .